2014
DOI: 10.5194/bg-11-1743-2014
|View full text |Cite
|
Sign up to set email alerts
|

Response of carbon dioxide emissions to sheep grazing and N application in an alpine grassland – Part 1: Effect of sheep grazing

Abstract: Abstract. Previous work has failed to address fully the response of (autotrophic and heterotrophic) respiration to grazing in different ecosystems, particularly in alpine grasslands outside the growing season. From 2010 to 2011 a field experiment combined two methods (static closed chambers and a closed dynamic soil CO 2 flux system) in alpine grasslands located in the Tianshan Mountains. We examined the effects of grazing regime on ecosystem respiration (R e ) both outside (NGS) and during (GS) the growing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To our knowledge, no previous study examined the different components of ER in response to the N addition gradient. Some studies conducted in alpine grassland demonstrated that N addition had no significant effects on ER (Jiang et al, 2013;Gong et al, 2014), since aboveground biomass did not respond to N addition in their studies. In this study, compared to the control treatment (without N addition), greater plant growth and aboveground biomass under N addition enhanced aboveground plant respiration and thus stimulated ER.…”
Section: Diverse Responses Of C Flux Components To the N Addition Gramentioning
confidence: 90%
“…To our knowledge, no previous study examined the different components of ER in response to the N addition gradient. Some studies conducted in alpine grassland demonstrated that N addition had no significant effects on ER (Jiang et al, 2013;Gong et al, 2014), since aboveground biomass did not respond to N addition in their studies. In this study, compared to the control treatment (without N addition), greater plant growth and aboveground biomass under N addition enhanced aboveground plant respiration and thus stimulated ER.…”
Section: Diverse Responses Of C Flux Components To the N Addition Gramentioning
confidence: 90%
“…CC-BY 3.0 License. conducted in alpine grassland demonstrated that N addition had no significant effects on ER (Jiang et al, 2013;Gong et al, 2014), since aboveground biomass did not respond to N addition in their studies. In this study, greater plant growth and aboveground biomass under N addition enhanced aboveground plant respiration and then stimulated ER.…”
Section: Diverse Responses Of C Flux Components To N Addition Gradientmentioning
confidence: 94%
“…In the third approach, the emissions of CO 2 or other gases are measured at targeted locations or times (Manley et al, 1995;Petersen et al, 1998;Cao et al, 2004;Parkin and Venterea, 2010;Gong et al, 2014). The collection of gas samples has been used to assess the fate of both N and C in a wide range of systems (Omonode et al, 2015;Chang et al, 2016a).…”
Section: A Rapid Methods For Measuring Feces Ammonia-nitrogen and Carbonmentioning
confidence: 99%